2018
DOI: 10.1177/0972150918788626
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Trends of Child Labour in India: Implications for Policy Reforms

Abstract: The article highlights the situation of child labour using the Census data of Government of India from 1971 to 2011. This study has also utilized the National Sample Survey Organization 68th round data on employment and unemployment of child labour in India. In this study, bivariate and multivariate analysis has been carried out. The chi-square test has been used to study the association between child labour and various socio-economic characteristics. The multiple logistic regression technique has been used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Senior citizens are also engaging in street vending. Currently, child labour has become a severe issue globally (Dash et al, 2018), and one aspect of this is that, in many countries, children are pushed towards street vending due to their socio-economic conditions (Estrada, 2012;Saxe, 1988;Ugochukwu et al, 2012). However, the evidence gathered for this perspective paper revealed that children's involvement in street vending activities is very low in Sri Lanka compared to the high involvement in other countries which is a good indicator of the socio-economic development of the country.…”
Section: Discussionmentioning
confidence: 81%
“…Senior citizens are also engaging in street vending. Currently, child labour has become a severe issue globally (Dash et al, 2018), and one aspect of this is that, in many countries, children are pushed towards street vending due to their socio-economic conditions (Estrada, 2012;Saxe, 1988;Ugochukwu et al, 2012). However, the evidence gathered for this perspective paper revealed that children's involvement in street vending activities is very low in Sri Lanka compared to the high involvement in other countries which is a good indicator of the socio-economic development of the country.…”
Section: Discussionmentioning
confidence: 81%
“…Defining child labour has always been a contested issue. The concept of "child" and "childhood" have changed over time and vary across cultures, social class, age and countries (Dash et al, 2018). Child labour is the combination of two words "child" and "labour", which have different meanings that vary across contexts.…”
Section: Conceptualising Child Labourmentioning
confidence: 99%
“…It is also estimated that 26% of children are engaged as cultivators, 32.9% as agricultural labourers, 5.2% as household industry workers and 35.8% as other workers. Previous studies have shown poverty as the primary factor of child labour that deprives children of education and causes school dropout (Sasmal and Guillen, 2015; Dash et al , 2018; Das and Das, 2009; Aggarwal, 2004). Mahendradev argues that the occurrences of child labour are dependent on several demand and supply-side factors (Mahendradev, 2004).…”
Section: Introductionmentioning
confidence: 99%